GainMomentum: powerful interactivity, slow video/data access. (user evaluation of SyBase Inc's GainMomentum 3.0 multimedia authoring tool) - Sullivan-Trainor, Michael (Computerworld, 1994)
According to users, Sybase Inc.'s GainMomentum 3.0 high-end multimedia authoring tool provides powerful features for quickly creating interactive applications. However, the ability to quickly incorporate video is lacking and the price was considered steep.